Life situation of a caregiver of a child with congenital heart defect and/or other cardiac problems: structure and preliminary validation of a new questionnaire - Kolarczyk, Ewelina; Morka, Aleksandra; Barański, Kamil; Szydłowski, Lesław (Frontiers in Psychology, 2023)
Background: Illness in a child with cardiac disease causes stress, brings additional responsibilities, reorganizes family life, and changes the functioning of the family. Aim: This study aimed to validate a new questionnaire evaluating the life situations of caregivers/parents of children with congenital heart disease (CHD) and/or other cardiac diseases (OCD). Materials and Methods: The questionnaire comprised 10 questions aimed at assessing the life situation of an ill child’s caregiver in two main areas: personal and spiritual. The total score of the questionnaire assessing the life situation of the caregiver of a child with a CHD and/or OCD can range from 0 to 32 points, with scores <26 indicating a poor, 25 to 32 indicating an average, and >32 indicating a good level of life situation in the personal sphere of the caregiver. The questionnaire was assessed using Cronbach’s alpha tests, and repeatability was assessed using Cohen’s Kappa test (retest) within a time interval of two to four weeks from the first measurement. Results: The research covered 50 respondents. Cohesion in the personal sphere obtained a satisfactory value of Cronbach’s α = 0.72, in the spiritual sphere: Cronbach’s α = 0.83, and the result common for both sections was: Cronbach’s α = 0.66. Conclusions: The Life Situation Assessment Questionnaire for caregivers of children with CHD and OCD is a reliable and homogeneous tool for measuring the functioning of parents in the event of a child’s illness.